Clinical profile of patients with post burn contracture - Tyagi, Arnav; Rajan, Manu; Dvivedi, Sanjay; Rawat, Kinnari A. V. (International Surgery Journal, 2018)
Background: Burns are a major, global public health problem, resulting in an estimated 195,000 deaths annually. Most burns occur in low-and middle-income countries, with almost half occurring in the south-east Asia region. The reasons for the high incidence include widespread ignorance of fire prevention, the rapid increase of poor socio-economic conditions, and the persistence of old traditions and customs. Methods: The study was carried out in Department of Surgery, Himalayan Institute of Medical Sciences, SRH University, Swami Ram Nagar, Dehradun over a period of 12months. Cases of the post burn contractures attended in the O.P.D were included in the study. Results: A total of 45 patients were included in the study. Of these, 22 (48.8%) were males and 23 (51.2%) were females. Ages ranged from 1 to 55year. Flame burn (20 cases = 44.4%) was the most common type of initial burn insult followed by scald burns (14 cases=31.1%). Conclusions: The pitfalls in initial burn care that lead to contractures in the patients include the failure to institute adequate surgical management of deep burns, the lack of physiotherapy/ROM exercises, and failure to provide proper anti-deformity splint age. There is need to revisit the prevalent acute burn care practices and establish focused preventive strategies.